EXAMINING POST GRADUDATE THESES IN NURSING IN TURKEY BETWEEN 1980-2015 - Dilek Büyükkaya BESEN (Rojan GÜMÜŞ, 2016)
The aim of this study is to examine post-graduate thesesin nursing in Turkey between 1980-2015 and to determine the distribution of theses according to years, research types and research topics. The study was carried out with documental analysis. Theses on the subject area were collected from National Theses Center of Turkish Council of Higher Education. When the research studies are analyzed, what draws attention is that nearly all of them are experimental or quasi-experimental studies. The researchers mostly examined organizational behaviors. Another topic examined in graduate theses was patient care. Most common third experienced subject in field of nursing was nursing education. According to our results 44,37% of postgraduate theses in nursing were conducted in 2007-2015, 34,46% in 2000-2006 and the others before 2000. While 33,33% of postgraduate theses in nursing focused on patient care in 2000-2006 this proportion increased to 44,18% in 2007-2015. 258 (38,16%) of 676 theses focused on patient care, 303 (44,82%) on organizational behavior and 115(17,01%) on nursing education. When distribution of research designs used in postgraduatetheses in nursing was analyzed 32,69% of theses were designed experimental, 18,78% quasi-experimental and 39,49 non-experimental. 6,80% of postgraduate theses were descriptive.